Research on Influencing Factors of Haidilao’s O2O Model Customer Satisfaction under the Background of the COVID-19 - Liu, Bin; Koompai, Somjintana (Science, Technology, and Social Sciences Procedia, 2022)
The O2O model of Haidilao plays an important role in breaking through the difficulties brought by the epidemic. Based on the existing customer satisfaction model and the COVID-19 background, this paper finds out the main factors that affect the customer satisfaction of the O2O model of Haidilao, and builds a satisfaction evaluation model that is more consistent with the COVID-19 background. In the process of indicator setting, the content of indicators at all levels was refined. Through questionnaire distribution, the evaluation and scoring of customers’ satisfaction with Haidilao were collected. Descriptive statistical analysis, correlation analysis and regression analysis were carried out on the data results, and 6 influencing factors were obtained: Platform quality, food quality, service quality, distribution quality, price level, marketing level and customer comprehensive satisfaction. It is hoped that it can provide some reference value for other catering enterprises in the same industry to improve customer satisfaction under O2O mode, and help the healthy development of catering enterprises.